MODIFIKASI PERMAINAN TRADISIONAL UNTUK MENINGKATKAN AKTIVITAS MOTORIK SISWA SD LUAR BIASA - Arifin, Bustanol; Muzakki, Abdurrohman; Suwandayani, Beti Istanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was motivated by the low participation of Special Needs Elementary School (SDLB) students in physical education activities, which hinders the optimal development of their gross motor skills. One contributing factor is the use of monotonous teaching methods that are less adaptive to the needs of students with special needs. This research aims to examine the effectiveness of a modified traditional jump rope game in improving the motor activity of SDLB students. The study employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, conducted in two cycles. The subjects were 20 students with various disabilities, including mild intellectual disabilities, autism, and learning difficulties. Each cycle consisted of planning, action, observation, and reflection stages. Data were collected through observation sheets measuring balance, movement coordination, leg strength, active participation, and movement independence. The results revealed significant improvements across all indicators from Cycle I to Cycle II. The percentage of students in the well-developed – very well-developed category increased from 65% to 90% for balance, from 70% to 85% for movement coordination, from 70% to 90% for leg strength, from 70% to 90% for active participation, and from 65% to 88% for movement independence. These findings demonstrate that the modified jump rope game effectively enhances gross motor skills, self-confidence, and student engagement. It is recommended that this strategy be implemented sustainably with adequate facilities and teacher training to design adaptive and enjoyable learning activities for students with special needs.